The role and therapeutic effectiveness of Plantago ovata seed husk (psyllium husk) in the prevention and non-pharmacological treatment of gastrointestinal diseases. Part 1. Clinical use of psyllium husk in the treatment of irritable bowel syndrome, ulcerative colitis, and colorectal cancer - Przybyszewska, Justyna; Kuźmiński, Andrzej; Przybyszewski, Michał; Popławski, Cezary (Gastroenterology Review/Przegląd Gastroenterologiczny, 2024)
Plantago ovata is a common medicinal plant widely cultivated in tropical regions of the world. The outer seed coat of P. ovata, obtained by cleaning the seeds, contains soluble and insoluble fibre in a ratio of 7:3, making products containing P. ovata husk an ideal source of health-beneficial fibre. The results of clinical trials demonstrate the therapeutic efficacy of psyllium husk for various gastrointestinal disorders. It has also been documented that psyllium ingestion exhibits antioxidant, immunomodulatory, antiproliferative, anticancer, and antiviral effects. Such pleiotropic effects of P. ovata husk are related to the presence in its composition of arabinoxylan, which forms a gel in an aqueous environment, as well as bioactive compounds and their metabolites. This article presents the evidence available in the literature on the therapeutic potential and possible mechanisms of action of psyllium in the treatment of irritable bowel syndrome and ulcerative colitis, and prevention of colorectal cancer.